Stigma resistance is associated with advanced stages of personal recovery in serious mental illness patients enrolled in psychiatric rehabilitation. Issue 11 (16th August 2022) - Dubreucq, J.; Plasse, J.; Gabayet, F.; Faraldo, M.; Blanc, O.; Chereau, I.; Cervello, S.; Couhet, G.; Demily, C.; Guillard-Bouhet, N.; Gouache, B.; Jaafari, N.; et al.
Abstract: Background: Stigma resistance (SR) is defined as one's ability to deflect or challenge stigmatizing beliefs. SR is positively associated with patient's outcomes in serious mental illness (SMI). SR appears as a promising target for psychiatric rehabilitation as it might facilitate personal recovery. Objectives: The objectives of the present study are: (i) to assess the frequency of SR in a multicentric non-selected psychiatric rehabilitation SMI sample; (ii) to investigate the correlates of high SR Methods: A total of 693 outpatients with SMI were recruited from the French National Centers of Reference for Psychiatric Rehabilitation cohort (REHABase). Evaluation included standardized scales for clinical severity, quality of life, satisfaction with life, wellbeing, and personal recovery and a large cognitive battery. SR was measured using internalized stigma of mental illness – SR subscale. Results: Elevated SR was associated with a preserved executive functioning, a lower insight into illness and all recovery-related outcomes in the univariate analyses. In the multivariate analysis adjusted by age, gender and self-stigma, elevated SR was best predicted by the later stages of personal recovery [rebuilding; p = 0.004, OR = 2.89 (1.36–4.88); growth; p = 0.005, OR = 2.79 (1.30–4.43)). No moderating effects of age and education were found. Conclusion: The present study has indicated the importance of addressing SR in patients enrolled in psychiatric rehabilitation. Recovery-oriented psychoeducation, metacognitive therapies and family interventions might improve SR and protect against insight-related depression. The effectiveness of psychiatric rehabilitation on SR and the potential mediating effects of changes in SR on treatment outcomes should be further investigated in longitudinal studies.